2010
DOI: 10.3109/1354750x.2010.533284
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic significance of ERCC1, thymidylate synthase and glutathione S-transferase P1 expression for advanced gastric cancer patients receiving adjuvant 5-FU and cisplatin chemotherapy

Abstract: The objective of this study was to determine whether the expressions of the excision cross-complementing (ERCC1), thymidylate synthase (TS) and glutathione S-transferase P1 (GSTP1) are predictive of clinical outcomes in advanced gastric cancer (AGC) patients receiving treatment with adjuvant 5-fluorouracil (5-FU) and cisplatin (FP) chemotherapy. One hundred forty nine patients were included in this study. ERCC1 and GSTP1 expression was correlated significantly with tumor size (p = 0.040, p = 0.018, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…As shown in several studies, both ERCC1 protein and mRNA expression are negatively correlated with the efficacy of platinum-based chemotherapy in patients with gastric cancer (Matsubara et al, 2008;Ozkan et al, 2010). In particular, in two recent studies of patients who received cisplatin-based adjuvant chemotherapy after curative resection, high ERCC1 expression was associated with decreased overall survival (OS) (Fareed et al, 2010;Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in several studies, both ERCC1 protein and mRNA expression are negatively correlated with the efficacy of platinum-based chemotherapy in patients with gastric cancer (Matsubara et al, 2008;Ozkan et al, 2010). In particular, in two recent studies of patients who received cisplatin-based adjuvant chemotherapy after curative resection, high ERCC1 expression was associated with decreased overall survival (OS) (Fareed et al, 2010;Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…High expression of ERCC1 in patients with advanced or metastatic gastric cancer has been associated with decreased survival in several studies, 12,13 whereas others have failed to demonstrate any association with ERCC1 expression and survival. 14 In 2 recent studies of patients who received adjuvant, cisplatin-based chemotherapy after curative intent resection, high tumor ERCC1 expression again was associated with decreased OS, 15,16 whereas a third study reported the opposite; namely, that increased ERCC1 expression was correlated with improved survival. 17 Thymidylate synthase (TS) is the rate-limiting enzyme in the pyrimidine nucleotide synthetic pathway for DNA and is a key target of fluoropyrimidine agents, such as 5-FU.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al (2010) reported that genetic polymorphisms of ERCC1-118C/C were associated with longer overall survival time of advanced gastric cancer patients treated with 5-FU-based combination chemotherapy. Another study conducted in Korea reported that ERCC1 expression was associated with tumor size, disease-free survival, and overall survival (Kim et al, 2011). However, the results conflict with those of 2 other studies (Yun et al, 2010;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, variants of ERCC1 play a role in the susceptibility to cancer. Previous studies indicated that variants of ERCC1 rs11615 have an impact on the clinical outcome of gastric patients receiving fluorouracil-based chemotherapy (Liang et al, 2010;Kim et al, 2011;Sonnenblick et al, 2012). Liang et al (2010) reported that genetic polymorphisms of ERCC1-118C/C were associated with longer overall survival time of advanced gastric cancer patients treated with 5-FU-based combination chemotherapy.…”
Section: Discussionmentioning
confidence: 99%